Penegakan Jarimah Misir dalam Qanun Jinayah Aceh serta Relevansinya dengan KUHP - Mazila Ayu Difani Tambunan,; Muhamad Azhar Alhafiz,; Muhammad Husen Haikal,; Deden Najmudin, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the enforcement of the crime of maisir in the Aceh Qanun on Jinayah and its relevance to the Criminal Code, as part of Aceh's special autonomy under Law Number 11 of 2006 concerning Aceh Governance. Islamic criminal law in Aceh, as stipulated in Qanun Number 6 of 2014 on Jinayat Law, integrates sharia norms such as jarimah or offenses and uqubah or punishments with the national legal system. The background of the research is driven by the dynamics of legal pluralism in Indonesia, where Aceh is the only province that formally applies sharia, creating challenges in harmonizing fiqh jinayah, namely hudud, qishas, tazir, and the Criminal Code, which prohibits gambling through Article 303 with imprisonment of up to 10 years. The normative juridical research method with a conceptual and implementative approach used library research, analyzing primary legal materials, secondary materials such as books and journals, and tertiary sources like legal dictionaries through descriptive analytical and comparative techniques. The results show that the Qanun Jinayah enriches law enforcement with a preventive and rehabilitative approach based on rahmatan lil alamin, where the uqubah maisir is more contextual, such as a maximum 45-month prison sentence for organizers, compared to the general provisions of the Criminal Code, although there is potential for jurisdictional conflict if not harmonized through judicial review. The conclusion of the research states that the Aceh model is relevant as a paradigm of regional autonomy, with recommendations to strengthen the academic drafts of qanuns and public participation to maintain the balance of Islamic identity, national legal certainty, and human rights.